Impact of Culinary Procedures on Nutritional and Technological Properties of Reduced-Fat Longanizas Formulated with Chia (Salvia hispanica L.) or Oat (Avena sativa L.) Emulsion Gel - Tatiana Pintado; Claudia Ruiz-Capillas; Francisco Jiménez-Colmenero; Ana M. Herrero (Foods, 2020)
This paper evaluates how grilling, a traditional culinary procedure for fresh meat products, affects the composition and technological properties of healthy longanizas formulated with chia (Salvia hispanica L.) (C-RF) and oat (Avena sativa L.) (O-RF) emulsion gels (EGs) as animal fat replacers. The use of EGs, regardless of whether they contain chia or oat, improved longaniza performance during cooking as they lost less (p < 0.05) water and fat. The composition of cooked sausages was affected by their formulation, particularly those with chia EG (C-RF) which featured the highest polyunsaturated fatty acid content, mainly due to the higher level of α-linolenic fatty acid (1.09 g/100 g of product). Chia and oat EGs in C-RF and O-RF allow longanizas to be labeled with nutritional and health claims under European law. In general, this culinary procedure increases (p < 0.05) the lightness, lipid oxidation and texture parameters of all samples.